The Effectiveness Of The Implementation Of The BPJS Health Program In Providing Services To Weak Economic Communities (Study At Helvetia District Health Center, Medan) - Jonathan Maruli Tua Sitompul (IHSA Institute, 2022)
The government formed an agency to provide free health services for the poor through the health insurance program. The application of the application of the national guarantee is carried out by BPJS Health. Based on this background the author is interested in writing this thesis to find out and understand how the effectiveness of the implementation of the BPJS Health program in providing services to the economically weak community at the Helvetia District Health Center, Medan. The method used in this study is a descriptive method with a qualitative approach. Data collection techniques with primary data collection in the form of interviews and field observations, and secondary data collection in the form of documentation and literature study. Determination of informants in this study using a purposive technique sampling. From the results of this research, it was concluded that in accordance with the analysis tools of the effectiveness indicators, namely, the objectives of program implementation, the accuracy of the methods and targets of program implementation, the success of program implementation, how to obtain resources in implementing the program, adequate facilities and infrastructure, the state of human resources ( Human Resources) are adequate, the performance of employees in providing services has been achieved quite well so that the implementation of the BPJS Health program at the Helvetia Health Center in providing services to the economically weak community is quite effective. However, there are still some obstacles that come from the community that must be overcome so that services can run well.